Do parents and children agree on rating a child's HRQOL? A systematic review and Meta-analysis of comparisons between children with attention deficit hyperactivity disorder and children with typical development using the PedsQLTM. Issue 3 (30th January 2019) - Lee, Yi-Chen; Yang, Hao-Jan; Lee, Wan-Ting; Teng, Ming-Jen
Abstract: Purpose: This meta-analysis was conducted to assess differences in a child's health-related quality of life (HRQOL) as reported by the child and their parents using the Pediatric Quality of Life Inventory TM, and the effects in both children with attention deficit hyperactivity disorder (ADHD) and those with typical development. Methods: Eight studies encompassing 16 independent groups met the inclusion criteria and were combined and compared in this meta-analysis. Fixed effect analysis was applied in the subgroup analysis to compare differences between children with ADHD and those with typical development. Results: Small to moderate magnitudes of parent-child discrepancies were found in the ratings of the children's HRQOL both in those with ADHD ( g  = −0.23 [−0.33, −0.13], p  < 0.001, physical HRQOL; g  = −0.60 [−0.71, −0.48], p  < 0.001, psychosocial HRQOL) and in those with typical development ( g  = −0.27 [−0.31, −0.23], p  < 0.001, physical HRQOL; g  = −0.29 [−0.33, −0.25], p  < 0.001, psychosocial HRQOL) except for emotional HRQOL in children with typical development ( g  = 0.003 [−0.04, 0.04], p  = 0.90). The parent-child discrepancy in rating the child's psychosocial HRQOL was significantly larger in the children with ADHD than in those with typical development. Conclusions and implications: This meta-analysis suggests that a child's HRQOL may be assessed in children and adolescents with ADHD both by parent proxy- and child self-reports. Parent-child discrepancies, especially in psychosocial HRQOL, and sources of discrepancy need to be addressed when assessing the child's HRQOL and planning interventions in children with ADHD. Implications for Rehabilitation: Parents reported a significantly worse health-related quality of life of their children than both the children with attention deficit hyperactivity disorder and those with typical development. A child's health-related quality of life needs to be assessed both by parent proxy and self-reports of the children. Children with attention deficit hyperactivity disorder and those with typical development differed significantly in parent-child discrepancy in child's psychosocial health-related quality of life, but not in physical health-related quality of life. Parent-child discrepancies, especially in psychosocial health-related quality of life, and sources of discrepancy (e.g., child, parent or family characteristics) need to be addressed when assessing the child's health-related quality of life and planning interventions in children with attention deficit hyperactivity disorder.